2021
DOI: 10.18662/mjesp/4.2/18
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Strengths Contributing to Rural Student’s Academic Performance in Kadazandusun

Abstract: Achieving academic success is a shared dream among students. To achieve academic success, psychological strengths, such as psychological well-being, academic self-efficacy, and motivation, are predictors of students’ academic achievement. To examine these factors, a study was conducted on rural students from the Kadazandusun community residing in the interior Sabah division. It is predicted that each of these psychological factors may contribute to the academic achievement of these rural students. There were 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In summary, psychological well-being theory emphasizes the positive effect of parental involvement on academic achievement. By providing emotional support, fostering a positive attitude towards education, setting high expectations, and being actively involved in their children's education, parents can significantly contribute to their children's psychological well-being, positively affecting their academic achievement (Grace, 2021). Therefore, parents need to prioritize their involvement in their children's education.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, psychological well-being theory emphasizes the positive effect of parental involvement on academic achievement. By providing emotional support, fostering a positive attitude towards education, setting high expectations, and being actively involved in their children's education, parents can significantly contribute to their children's psychological well-being, positively affecting their academic achievement (Grace, 2021). Therefore, parents need to prioritize their involvement in their children's education.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological correlations between dyspnea, hyperventilation and anxiety have also been described (Apostu, 2021;Ah Gang, 2020;Busu & Teodorescu, 2017;Oleshko, 2020). Physiological studies have shown that respiratory rate is raised by anxiety and that polypnea associated with shallow breathing resulting from anxiety attack aggravates dyspnea in COPD (O'Donnell, et al, 2007;Voicu et al, 2020).…”
Section: Anxiety and Copdmentioning
confidence: 90%